URBAN STORMWATER QUALITY AND QUANTITY IN THE CITY OF TALLINN - Bharat Maharjan; Karin Pachel; Enn Loigu (European Scientific Journal, ESJ, 2013)
This study aimed to provide an overview of stormwater quality and quantity, the impact on waterbodies and the likelihood of its usage in stormwater management. The potential impacts were assessed using statistical analysis following HELCOM, EU Directive and Estonian requirements. Further, Seasonal behaviour, variability, tentative sample size and frequency were examined using strongly dependent parameters obtained from correlation studies. Results show that the average concentrations of pollutants are not extremely high except microbiological parameters. Most basins have positive correlation of 0.4 - 0.6 between flow and suspended solids (SS), as well as of 0.4 - 0.95 between total phosphorus (TP) and SS. As for seasonal variation, large amount of SS is transported in spring whereas in summer, runoff and SS are consistent against winter and autumn. However, at a 70% confidence interval, there is considerable uncertainty in the mean flow and concentrations. Flow and SS have higher uncertainty than conductivity, BOD7, total nitrogen (TN) and TP. It was discovered that most of the samples belong to a small range of daily rainfall (<5 mm) and there is no measurement for first flush. Variability and inadequate representation of rainfall range calls for comprehensive sampling and validation of the data intended to use in stormwater management programs.